2004
DOI: 10.1097/01.cad.0000132230.51759.8d
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon-α2b treatment in melanoma patients: influence on amino acids, 5-hydroxyindolacetic acid and pteridine plasma concentrations

Abstract: Our objective was to study the influence of pegylated interferon-alpha2b (PEG-IFN-alpha) on the metabolism of amino acids and pteridines. We used an exploratory study into plasma concentrations of large neutral amino acids, 5-hydroxyindolacetic acid (5-HIAA), total biopterin (BIOP) and neopterin (NEOP) in 40 high-risk melanoma patients. Patients were randomized to treatment with PEG-IFN-alpha once a week in a dose of 6 microg/kg/week s.c. during 8 weeks, followed by a maintenance treatment of 3 microg/kg/week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
5
6
0
Order By: Relevance
“…The results of this prospective study confirmed earlier findings of our own previous retrospective studies and studies of others on the relation between IFN-␣ treatment and the TRP metabolism [5,[10][11][12] . Clearly, treatment with (PEG) IFN-␣ decreased TRP concentrations at all time points and TRP/LNAA ratios at 2 out of 3 time points, as a consequence of which diminished TRP availability to the CNS and consequent decrease in 5-HT synthesis in the short and in the long term can be expected.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The results of this prospective study confirmed earlier findings of our own previous retrospective studies and studies of others on the relation between IFN-␣ treatment and the TRP metabolism [5,[10][11][12] . Clearly, treatment with (PEG) IFN-␣ decreased TRP concentrations at all time points and TRP/LNAA ratios at 2 out of 3 time points, as a consequence of which diminished TRP availability to the CNS and consequent decrease in 5-HT synthesis in the short and in the long term can be expected.…”
Section: Discussionsupporting
confidence: 82%
“…As TRP competes with the other large neutral amino acids (LNAA) to the CNS, the TRP/LNAA ratio is a parameter considered to reflect the availability of TRP to the CNS. Accordingly, the TRP/ LNAA ratio has previously been found to be lowered in some studies in patients treated with IFN-␣ [8, 10,11] . The hypothesis that altered TRP metabolism is involved in IFN-␣ -induced depression is further supported by the observation that several studies performed in patients treated with IFN-␣ found significant correlations between measures for depression and a decrease in TRP concentrations [5,8,12] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Neopterin determination has been used to monitor systemic effects of cytokine therapy in melanoma patients. Neopterin concentrations increased significantly after the administration of interferon-alpha or interleukin-2 alone or in combination with chemotherapy (17)(18)(19)(20). In some of these studies, the increase in neopterin concentrations was accompanied by decreased tryptophan or increased kynurenine that reflect the activity of another IFN-γ-induced enzyme, indoleamine (2,3)-dioxygenase (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%